2, 6‐Bis(diazaboryl)pyridine – A Ligand with Hemilabile Donor and Lewis Acid Functionalities. Issue 4 (17th December 2019) - Schröder, Jan; Böttcher, Tobias
Abstract : The coordination chemistry of 2, 6‐bis(diazaboryl)pyridine (dab2 py) is studied towards selected halides of aluminum(III), gallium(III) and germanium(II). Addition of dab2 py to AlBr3 readily yielded the salt of ligand induced ionization [(dab2 py)AlBr2 ][AlBr4 ]. The aluminum atom in the cation is coordinated by the pyridine's nitrogen atom and also by one nitrogen atom of each diazaboryl group, resembling the coordination motif found for tridentate pincer ligands, e.g. 2, 6‐diiminopyridines. By NMR spectroscopic measurements a rapid exchange reaction between all four Ndab ‐atoms was detected, showing that the tridentate coordination motif of dab2 py is less rigid compared with 2, 6‐diiminopyridines. The adduct formation of dab2 py and GaCl3 does not proceed at room temperature in solution. Addition of GeCl2 · dioxane to this mixture gave the salt [(dab2 py)GeCl][GaCl4 ]. The germanium atom is coordinated by the pyridine's nitrogen atom and a nitrogen atom of one diazaboryl group. The product of partial hydrolysis of the cation [(dab2 py)GeCl] + was isolated as single crystals. The structure determination revealed the insertion of an oxygen atom between the germanium atom and a boron atom, showing that the diazaboryl groups do not only provide hemilabile Lewis donor but also weak Lewis acid functionalities that are involved in the stabilization of main group cations. Abstract : The coordination chemistry of 2, 6‐bis(diazaboryl)pyridine (dab2 py) was studied with selected main group compounds. The nitrogen atoms and the boron atom of the diazaboryl groups were found to be involved in the coordination chemistry. The system dab2 Py/GaCl3 was identified as a formal FLP at room temperature that allows for the synthesis of cationic main group element adducts.